Gaps in the implementation and uptake of maternal nutrition interventions in antenatal care services in Bangladesh, Burkina Faso, Ethiopia and India. Issue 2 (23rd November 2021) - Sanghvi, Tina; Nguyen, Phuong H.; Tharaney, Manisha; Ghosh, Sebanti; Escobar‐Alegria, Jessica; Mahmud, Zeba; Walissa, Tamirat; Zafimanjaka, Maurice; Kim, Sunny
Abstract: Antenatal care (ANC) is the largest health platform globally for delivering maternal nutrition interventions (MNIs) to pregnant women. Yet, large missed opportunities remain in nutrition service delivery. This paper examines how well evidence‐based MNIs were incorporated in national policies and programs in Bangladesh, Burkina Faso, Ethiopia and India. We compared the nutrition content of ANC protocols against global recommendations. We used survey data to elucidate the coverage of micronutrient supplementation, weight gain monitoring, dietary and breastfeeding counselling. We reviewed literature, formative research and program assessments to identify barriers and enabling factors of service provision and maternal nutrition practices. Nutrition information in national policies and protocols was often fragmented, incomplete and did not consistently follow global recommendations. Nationally representative data on MNIs in ANC was inadequate, except for iron and folic acid supplementation. Coverage data from subnational surveys showed similar patterns of strengths and weaknesses. MNI coverage was consistently lower than ANC coverage with the lowest coverage of weight gain monitoring and variable coverage of dietary and breastfeeding counselling. Key common factors associated with coverage were micronutrient supply disruptions; suboptimal counselling on maternal diet, weight gain, and breastfeeding; and limited or no record keeping. Adherence of women to micronutrient supplementation and dietary recommendations was low and associated with late and too few ANC contacts, poor maternal knowledge and self‐efficacy, and insufficient family and community support. Models of comprehensive nutrition protocols and health systems that deliver maternal nutrition services in ANC are urgently needed along with national data systems to track progress. Key points: Delivering nutrition services to all pregnant women is essential for maternal and child health outcomes but remains a challenge. Nutrition gaps in antenatal care (ANC) include lack of specificity in national guidelines and protocols, bottlenecks in micronutrient supplies, low ANC provider knowledge and skills, inadequate supervision to reinforce counseling, and not engaging families to encourage key practices. National protocols for ANC should be more specific for the four nutrition interventions (micronutrient supplements, weight gain monitoring, counseling on diets and counseling on breastfeeding) and assign accountability for coverage and quality. Country models are needed for improving provision and utilisation of nutrition interventions through ANC that are based on comprehensive policy frameworks.